Interaction with mLin-7 Alters the Targeting of Endocytosed Transmembrane Proteins in Mammalian Epithelial Cells - Straight, Samuel W. (The American Society for Cell Biology, 2001)
To investigate the targeting mechanism for proteins bound to the mammalian Lin-7 (mLin-7) PDZ domain, we created receptor protein chimeras composed of the carboxyl-terminal amino acids of LET-23 fused to truncated nerve growth factor receptor/P75. mLin-7 bound to the chimera with a wild-type LET-23 carboxyl-terminal tail (P75t-Let23WT), but not a mutant tail (P75t-Let23MUT). In Madin-Darby canine kidney (MDCK) cells, P75t-Let23WT localized to the basolateral plasma membrane domain, whereas P75t-Let23MUT remained apical. Furthermore, mutant mLin-7 constructs acted as dominant interfering proteins and inhibited the basolateral localization of P75t-Let23WT. The mechanisms for this differential localization were examined further, and, initially, we found that P75t-Let23WT and P75t-Let23MUT were delivered equally to the apical and basolateral plasma membrane domains. Although basolateral retention of P75t-Let23WT, but not P75t-Let23MUT, was observed, the greatest difference in receptor localization was seen in the rapid trafficking of P75t-Let23WT to the basolateral plasma membrane domain after endocytosis, whereas P75t-Let23MUT was degraded in lysosomes, indicating that mLin-7 binding can alter the fate of endocytosed proteins. Altogether, these data support a model for basolateral protein targeting in mammalian epithelial cells dependent on protein–protein interactions with mLin-7, and also suggest a dynamic role for mLin-7 in endosomal sorting.